CD8 T cells are essential for recovery from a respiratory vaccinia virus infection - Goulding, John (2012)
The precise immune components required for protection against a respiratory Orthopoxviridae infection, such as human smallpox or monkey pox, remain to be fully identified. In this study we utilized the virulent Western Reserve strain of vaccinia virus (VACV-WR) to model a primary respiratory Orthopoxviridae infection. Naïve mice infected with VACV-WR mounted an early CD8 T cell response, directed against dominant and subdominant VACV-WR antigens, followed by a CD4 T cell and immunoglobulin (Ig) response. In contrast to other VACV-WR infection models that highlight the critical requirement for CD4 T cells and Ig, we found that only mice deficient in CD8 T cells presented with severe cachexia, pulmonary inflammation, viral dissemination and 100 % mortality. Depletion of CD8 T cells at specified times throughout infection highlighted that CD8 T cells perform their critical function between days four and six post infection and that their protective requirement is critically dictated by initial viral load and virulence. Finally, the capacity of adoptively transferred naïve CD8 T cells to protect RAG (-/-) mice against a lethal VACV-WR infection demonstrated that CD8 T cells are both necessary and sufficient in protecting against a primary VACV-WR infection of the respiratory tract.